Analyzing The Effect Of Customer Satisfaction, Service Quality, And Brand Image On Customer Loyalty In E-Commerce Platforms - Palupi, Murraya Putri; Muafiq, Farikhul (Journal Management & Economics Review (JUMPER), 2025)
The rapid growth of e-commerce platforms has significantly transformed consumer shopping behavior, making customer loyalty a key competitive advantage in the digital marketplace. This study investigates the effects of customer satisfaction, service quality, and brand image on customer loyalty in the context of e-commerce. Using a quantitative approach, primary data were collected through a structured questionnaire from 250 active e-commerce users. Data analysis was conducted using multiple linear regression to examine the relationships among the variables. The results reveal that all three factors—customer satisfaction, service quality, and brand image—have a significant and positive impact on customer loyalty. Notably, brand image emerged as the most influential predictor, underscoring the importance of emotional and psychological associations with the brand in retaining customers. These findings suggest that e-commerce platforms must prioritize delivering superior service experiences, maintaining high customer satisfaction levels, and strategically managing their brand image to foster long-term loyalty. This study contributes to the growing literature on digital consumer behavior and provides practical insights for e-commerce managers and marketers seeking to enhance customer retention.